1979
DOI: 10.1111/j.1445-5994.1979.tb04165.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular System in Paget's Disease of Bone and the Response to Therapy with Calcitonin and Diphosphonate

Abstract: Summary: The cardiovascular system in Paget's disease of bone and the response to therapy withcalcitonin and diphosphonate. J. W. Henley, R. S. Croxson and H. K. Ibbertson, Aust. N.Z. J. Med., 1979, 9, pp. 390–397. The cardiovascular status of 39 patients with Paget's disease of bone was studied before and after treatment with porcine calcitonin or diphosphonate (disodium etidronate). Cardiovascular abnormalities were detected in 32 patients. Systemic hypertension was present in four, ischaemic heart disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The use of the calcitonin and the diphosphonate has attained the most widespread acceptance, but mithramycin, and the combination of thiazide diuretics and calcium supplements are still used but are less adequately evaluated [48]. The cardiovascular effects of Paget's disease have been shown to respond rapidly to treatment with calcitonin and more slowly with diphosphonate [32,48].…”
Section: Paget's Disease Of Bone and Polyostotic Fibrous Dysplasiamentioning
confidence: 97%
See 1 more Smart Citation
“…The use of the calcitonin and the diphosphonate has attained the most widespread acceptance, but mithramycin, and the combination of thiazide diuretics and calcium supplements are still used but are less adequately evaluated [48]. The cardiovascular effects of Paget's disease have been shown to respond rapidly to treatment with calcitonin and more slowly with diphosphonate [32,48].…”
Section: Paget's Disease Of Bone and Polyostotic Fibrous Dysplasiamentioning
confidence: 97%
“…The increased cardiac output is presumably related to multiple, small systemic arteriovenous fistulae in the bones involved by these disorders, which lower peripheral resistance [32][33][34]. The increased cardiac output is proportional to the amount of skeletal involvement.…”
Section: Paget's Disease Of Bone and Polyostotic Fibrous Dysplasiamentioning
confidence: 98%
“…Cardiovascular, 34–36 arthritic, 37–39 and neoplastic 40,41 problems have been reported previously in patients with Paget's disease. We observed that the Paget's population reported a greater percentage of arthritic and osteoporotic problems than did the controls.…”
Section: Discussionmentioning
confidence: 83%
“…Bony hypervascularity, present to some extent in all patients with Paget's disease, is believed to cause the warmth of the skin overlying bone in many patients. With extensive skeletal involvement cardiac output is increased; this can lead to high‐output heart failure or, more commonly, to exacerbation of any underlying congestive heart failure or ischemic heart disease 24 …”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…The calcitonins, because of their rapidity of action, are most appropriate for patients with severe symptoms who need rapid relef? 26–29 Treatment is usually continued for rune to 12 months, and additional courses are often given for symptomatic relapses. Most patients experience symptomatic relief from calcitonin therapy after two to eight weeks, and dramatic improvements in neurologic and cardiovascular complications have been reported 19,20,24,32 . Effects on biochemical determinations usually reach a plateau after six to eight weeks of therapy; most patients achieve about 50 per cent reductions of pretreatment abnormalities.…”
Section: Managementmentioning
confidence: 99%